Judiciary Analysis of Consumer Lawsuits Against Businesses Reviewed from The Consumer Protection Law and The Civil Code - Nanang Kurniawan; Hanifah Febriani (Proceeding International Conference Restructuring and Transforming Law, 2023)
Normatively, consumer protection law is regulated in the Consumer Protection Law (UUPK) Number 8 of 1999 where the law is an important legal basis for consumers in Indonesia. The purpose of this study is to find out about consumer protection laws in providing legal protection to consumers from lawsuits by business actors, and to find out the legal review of lawsuits by business actors against consumers seen from the Civil Code. In achieving the research objectives, the researchers used normative juridical methods using secondary data. The approach used is the statutory approach. In achieving the research objectives, the researchers used descriptive analytical methods. The results of the study are 1. Consumer lawsuits that have been harmed are reviewed based on the Consumer Protection Act Article 23 of the Consumer Protection Law Number 8 of 1999 with the settlement of disputes against consumer claims that have been harmed reviewed based on the Consumer Protection Law Articles 45 and Article 47. 2. Lawsuits consumers who are harmed are reviewed based on the Civil Code Articles 1313 and 1314 with the settlement of disputes claimed by consumers who are harmed reviewed based on Articles 1338 and 1365.